2019
DOI: 10.3390/en12173247
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Short-Term BIPV Power Predictions Using Feature Engineering and a Recurrent Neural Network

Abstract: The time resolution and prediction accuracy of the power generated by building-integrated photovoltaics are important for managing electricity demand and formulating a strategy to trade power with the grid. This study presents a novel approach to improve short-term hourly photovoltaic power output predictions using feature engineering and machine learning. Feature selection measured the importance score of input features by using a model-based variable importance. It verified that the normative sky index in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
(33 reference statements)
2
1
0
Order By: Relevance
“…However, it can be concluded that the results obtained in our work, and results of other authors [2,13,17,22], are similar in terms of accu-racy: the deviation of the predicted power from the actual power is not greater than a few percent.…”
Section: Comparison Of the Resultssupporting
confidence: 84%
“…However, it can be concluded that the results obtained in our work, and results of other authors [2,13,17,22], are similar in terms of accu-racy: the deviation of the predicted power from the actual power is not greater than a few percent.…”
Section: Comparison Of the Resultssupporting
confidence: 84%
“…The non-measured features, namely the sun angles and day of year, have low relevance probably because the periodic information that they introduced is included in other features such as irradiance. Wind speed and precipitation are the two least relevant features, which coincides with previous results reported in literature (Abuella and Chowdhury, 2017;Kuzmiakova et al, 2017;Lee et al, 2019). One surprising result is the low importance of ambient temperature, which is usually amongst the chosen features (Abuella and Chowdhury, 2017;Kuzmiakova et al, 2017;Lee et al, 2019).…”
Section: Feature Selectionsupporting
confidence: 87%
“…Wind speed and precipitation are the two least relevant features, which coincides with previous results reported in literature (Abuella and Chowdhury, 2017;Kuzmiakova et al, 2017;Lee et al, 2019). One surprising result is the low importance of ambient temperature, which is usually amongst the chosen features (Abuella and Chowdhury, 2017;Kuzmiakova et al, 2017;Lee et al, 2019).…”
Section: Feature Selectionsupporting
confidence: 87%
“…To overcome the size problem, modifications of the DL-based models were proposed in [34][35][36][37][38]. The authors developed deep RNNs and LSTM-based pure and hybrid models using real weather time-series and synthetic data to predict short-term (i.e., 1 h to 4 h) and very-short-term PV power production (i.e., 1 to 15 min).…”
Section: Introductionmentioning
confidence: 99%